Enhancing the quality of e-learning by implementing Quality Matters standards - Zahra Alqahtani (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية)
The use of e-learning technologies is gaining momentum in educational institutions in all parts of the world, including Saudi universities. In the e-learning context, there is a growing need and concern among Saudi universities to improve and enhance the quality assurance of e-learning systems. Applying quality assurance practices and applying quality standards in e-learning in Saudi universities is thought to help to reduce the negative viewpoints of some stakeholders and ensure stakeholders’ satisfaction that their needs are met. To understand how quality assurance standards improve e-learning methods in Saudi universities, this study explored and investigated strategies for the development of quality assurance in e-learning in King Khalid in Saudi Arabia,which is considered a good reference university using ongoing best practices in e-learning systems among Saudi universities. The university adopted Quality Matters Standards as a controlling guide for the quality of its blended and full e-course electronic courses. This qualitative research involved the use of different types of interviews (n=30), as well as analysis of documents that contain data related to e-learning methods in the Saudi university environment. The results revealed that e-course design was a supportive factor which helped to ensure the quality of e-learning in the Saudi university environment.